One summer at Camp Winston - Shopsowitz, Karen; documentary (Television station : Canada); Moviewitz Productions Inc.; FeelSales (Firm) ([Toronto, Ontario] : documentary : Moviewitz Productions Inc., 2010)
At Camp Winston, uniqueness truly is the norm. The camp accepts children with complex neurological disorders, that include Autism, Tourette Syndrome, and Asperger's Syndrome. Filmed against the backdrop of a beautiful Muskoka, Canada summer, these children, so often branded as different, are given the opportunity to grow a little, have a bit of fun, learn, and be embraced for exactly who they are. --
Originally released as a motion picture in 2010.
Cinematographer, Marc J. Landau ; editor, Karen Shopsowitz ; music, Mike Plume.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 30, 2020)
Keywords: Camp Winston (Kilworthy, Ontario); Muskoka (Ont. : District municipality); Nervous system -- Diseases; Documentary films; Nonfiction films; Internet videos; Streaming video